Remittances and inequality: A dynamic migration model - Frederic Docquier; Hillel Rapoport; I-Ling Shen (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2006)
We develop a model to study the effects of migration and remittances on inequality in the origin communities. While wealth inequality is shown to be monotonically reduced along the time-span, the short- and the long-run impacts on income inequality may be of opposite signs, suggesting that the dynamic relationship between migration/remittances and inequality may well be characterized by an inverse U-shaped pattern. This is consistent with the findings of the empirical literature, yet offers a different interpretation from the usually assumed migration network effects. With no need to endogenize migration costs through the role of migration networks, we generate the same result via intergenerational wealth accumulation.
Keywords: O11; O15; J61; D31; 330; Migration; remittances; inequality